What is the De facto? Implementation of the Flipped Classroom Method in Higher Education: Veteran Professors Share Their Experiences over Multiple Years - ElGamal, Hebatullah (Online Learning, 2025)
The flipped classroom approach is an innovative and effective alternative to traditional teaching practices. However, there needs to be more research on its long-term impact. A qualitative research study examined the implementation of flipped learning on the long term by interviewing expert professors from various academic institutions across the globe. The study included professors from STEM and Education Sciences disciplines with significant records of scholarly publications on flipped learning methods and years of experience flipping their university classes. The themes and codes were derived from their opinions, and the results revealed that educators consider this method a valuable and effective tool for providing feedback and promoting active learning strategies. However, obstacles to implementing this method include traditional teaching culture, resistance to change, and unprepared students. The study highlights the importance of successfully guiding educators to implement flipped learning and informing higher education policy. However, obstacles to implementing this method include traditional teaching culture, resistance to change, and unprepared students. Keywords: Flipped classroom, Flipped Learning, Higher Education, long-term implementation.